2018
DOI: 10.1088/2399-6528/aa9c50
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electric charge on anisotropic compact stars in conformally symmetric spacetime

Abstract: We obtain a new class of interior solutions for charged anisotropic stars which admits non-static conformal motion. The Einstein-Maxwell field equations are solved by taking a physically reasonable choice for the g rr metric co-efficient and a suitable expression for charge density. From the analysis we have shown that there is a central singularity on space-time by calculating Kretschmann scalar though the central density and central pressure are finite. The emphasis are given on the causality condition and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…The anisotropic distributions, where charge is absent, correspond to the results of Rahaman et al [35], Rahaman et al [36], Shee et al [14], Mafa Takisa et al [16], Esculpi and Aloma [37]. Models with both charge and anisotropy, include particular exact solutions of Esculpi and Aloma [37] and Newton Singh et al [15]. It is clear that other exact solutions can be generated by considering other functional forms of the anisotropy Δ and charge E. Our general conformal solution provides a unifying basis for particular solutions that exist.…”
Section: Known Solutionssupporting
confidence: 76%
See 1 more Smart Citation
“…The anisotropic distributions, where charge is absent, correspond to the results of Rahaman et al [35], Rahaman et al [36], Shee et al [14], Mafa Takisa et al [16], Esculpi and Aloma [37]. Models with both charge and anisotropy, include particular exact solutions of Esculpi and Aloma [37] and Newton Singh et al [15]. It is clear that other exact solutions can be generated by considering other functional forms of the anisotropy Δ and charge E. Our general conformal solution provides a unifying basis for particular solutions that exist.…”
Section: Known Solutionssupporting
confidence: 76%
“…Shee et al [14] found anisotropic compact relativistic stars with nonstatic conformal symmetry. Newton Singh et al [15] discovered electrically charged dense stars in the presence of a static conformal Killing vector. Mafa Takisa et al [16], Kileba Matondo et al [17] and Kileba Matondo et al [18] generated new stellar models with conformal symmetries with radii, masses, densities and redshifts which are consistent with observed astronomical objects.…”
Section: Introductionmentioning
confidence: 99%
“…The third method is using conformal killing vector. Here the bridge equation is [56], [57], [58], [59]eν=c2r2exptrue(badbreakafter−2kBeλfalse/2rdrtrue) where A , B , C and k are constants. We can see that the second and third method are very much similar except one is with normalcosh2 and other with exponential function.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few results have been found for compact objects, and only for the special case of a conformal Killing vector. Shee et al [19], and Newton Singh et al [20] analytically obtained new exact spherically symmetric solutions with conformal geometry for compact stars in strong gravitational fields. We expect that a comprehensive analysis of conformal symmetries will provide deeper insights into many other astrophysical situa-tions.…”
Section: Introductionmentioning
confidence: 99%